The Urgency of Amicus Curiae in The Indonesian Law (A Case Study of the 2024 Presidential Election Dispute) - Sulistyowati; Mery, Lisa; Maharani, Dewi Nadya; Andika, Andi (Alauddin Law Development Journal (ALDEV), 2024)
One of the authorities of the Constitutional Court (MK) is to resolve disputes over general election results. In the 2024 presidential election, the presidential candidate pair Anies Baswedan-Muhaimin and the Ganjar-Mahfud pair filed a lawsuit with the Constitutional Court. This study uses normative research. The results show that many figures have emerged as Amicus Curae, such as Megawati Soekarnoputri, Dien Syamsudin and others. In addition, this Amicus Curae is very important in order to achieve openness and justice in general election disputes in the Indonesian legal system.